The eve of destruction? Local groups and large-scale networks during the late fourth and early third millennium BC in central Europe - Hofmann, Daniela; Mischka, Doris; Scharl, Silviane (sidestone press, 2025)
This volume collects papers on the pre-Corded Ware horizon in central Europe and adjacent areas (i.e. from c. 3500 – 2800 BC). This phase is very patchily researched, partly also because certain kinds of evidence, notably domestic architecture and burials, are rare or absent in many regions. This has occasionally been interpreted as signs of a major crisis and population bottleneck, which in turn facilitated the migration of new populations from the steppe, bringing with them amongst others new economic regimes, ideologies and settlement patterns. Research over the last few years has shown that this scenario needs to be nuanced. Although evidence remains scattered, a picture of regional diversity is emerging, with probably mobile but well-connected Late Neolithic societies undergoing social changes of their own, and instituting several key innovations long before the appearance of the Corded Ware. This volume offers a selection of such case studies, comprising amongst others an overview over the steppe background of new mortuary practices, contributions on settlement and changing networks in Switzerland, Poland and several regions of Germany, as well as discussions on the spread of pottery innovations and lithic material, the possible effect of droughts on Late Neolithic societies, new patterns of monumentality and figurative expression, the social role of battle axes, networks of influences visible in burial rites, and the possibility for “parallel societies” with different modes of life. An introductory chapter draws out central themes. Together, these contributions show that the transition to the Corded Ware culture was a diverse and multi-facetted process, with many continuities across the transitio